Responses in Phenotypic Plasticity of Amaranthus palmeri and Polygonum orientale to Soil Factors under Different Habitats. Issue 1 (9th December 2019) - Zhang, Mei; Ma, Kexin; Liu, Tong; Tang, Lili; Khan, Amir Abdullah; Yang, Tong; Zheng, Pufan; Wang, Tongtong; Han, Jianhua; Shi, Fuchen
Abstract: The extension and structure of functional traits variation in response to different soil factors between invasive and native plants are poorly understood. Functional traits and soil factors of the invasive plant Amaranthus palmeri and its coexisting plant Polygonum orientale are investigated under three heterogeneous habitats: roadside (rs), wasteland (wl), and riverbank (rb) in Tianjin, China. The shoot dry weight (SDW) and leaf nitrogen (LN) of A. palmeri are significantly higher compared with P. orientale, while A. palmeri has significantly lower leaf dry weight (LDW), leaf area (LA), leaf carbon (LC), and leaf C/N ratio under different habitats. The larger phenotypic plasticity of A. palmeri is one of the important reasons for their successful invasion to heterogeneous habitats. Similarly, the soil water content (SWC) of both species shows a significant difference ( p < 0.05) with maximum in riverbank habitat to lowest in roadside habitat. Soil N/P ratio, C/N ratio, and C/P ratio of rb habitats are significantly lower compared to wl and rs habitats ( p < 0.05). A redundancy analysis indicates that SWC is the dominant soil factor affecting the functional traits of A. palmeri and P. orientale . However, A. palmeri forms an environmental adaptation strategy by changing traits of SDW, LN, and leaf C/N ratio, which is different from P. orientale by changing traits of LA and LDW. Abstract : Plant functional traits and soil factors of the invasive plant Amaranthus palmeri and its coexisting plant Polygonum orientale are investigated under three heterogeneous habitats: roadside, wasteland, and riverbank in Tianjin, China. Analyses indicate that the larger phenotypic plasticity (SDW, LDW, LA, LN, LC) of A. palmeri is one of the important reasons for the successful invasion to heterogeneous habitats.